2021
DOI: 10.3390/jcm10112494
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Fear of Infection and Insomnia among Dentists from Oradea Metropolitan Area during the Outbreak of Sars-CoV-2 Pandemic

Abstract: Various studies have shown the impact of COVID-19 pandemic on mental health, identifying that people with a strong fear of getting infected are more prone to become stressed, depressed, anxious and to experience sleeping disturbance. The present study focuses on the impact of fear of COVID-19 and its relationship with insomnia among dentists. 83 dentists from public and private clinics were included in the research. A questionnaire was especially constructed for this study, consisting of three parts: the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 61 publications
2
15
0
1
Order By: Relevance
“…There is a positive significant association between preventive practice regarding COVID‐19 and fear of COVID‐19 among our participants. This finding concurs with a study done in Romania which reported that the practice of preventive behaviors regarding COVID‐19 had a significant positive association with fear of COVID‐19 (Iorga et al, 2021). The explanation might be that fear of COVID‐19 may motivate people to engage in behaviors that prevent them from infection.…”
Section: Discussionsupporting
confidence: 92%
“…There is a positive significant association between preventive practice regarding COVID‐19 and fear of COVID‐19 among our participants. This finding concurs with a study done in Romania which reported that the practice of preventive behaviors regarding COVID‐19 had a significant positive association with fear of COVID‐19 (Iorga et al, 2021). The explanation might be that fear of COVID‐19 may motivate people to engage in behaviors that prevent them from infection.…”
Section: Discussionsupporting
confidence: 92%
“…The second, habituation, denotes a process in which in which a perpetual exposure to a risk tends to decrease the anxiety of people towards the risk ( Foa and Kozak, 1986 ; Guazzini et al, 2022 ). Regarding habituation, our data highlight that since pandemic anxiety reduce throughout time, individuals might need additional motivational strategies to continuously engage in preventive behaviors ( Iorga et al, 2021 ; Scrima et al, 2022 ). On the other hand, considering that pandemic anxiety is associated with mental suffering ( Karadem et al, 2021 ), assessing intolerance of uncertainty, the fear about others being infected by COVID-19, and the fear of having the mental health impacted by COVID-19 may be crucial for treating mental health suffering in the pandemic scenario.…”
Section: Discussionmentioning
confidence: 94%
“…The COVID-19 anxiety is one of the cognitive and emotional process responsible for this impact, associated with psychological distress, anxiety, and depressive symptoms ( Karadem et al, 2021 ). On the other hand, COVID-19 anxiety is associated with mitigation behaviors and intention to get vaccinated ( Iorga et al, 2021 ; Scrima et al, 2022 ). Understanding how the pandemic anxiety varies along the pandemic situation could contribute to understanding the development of coping strategies in face of a new stressor.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside, numerous predictors like knowledge of mucormycosis, age, gender, profession, and FNF died of COVID-19 were found significantly associated with mucormycosis fear. Albeit, the fear of infectious diseases during the outbreak has been recorded previously in many studies in various aspects [37]–[40].…”
Section: Discussionmentioning
confidence: 99%